Channel Mobility and Inversion Carrier Density in MFIS FEFET: Deep Insights Into Device Physics for Non-Volatile Memory Applications - Song-Hyeon Kuk; Kyul Ko; Bong Ho Kim; Joon Pyo Kim; Jae-Hoon Han; Sang-Hyeon Kim (IEEE Journal of the Electron Devices Society)
Ferroelectric polarization charge in doped-HfO2 such as HfZrOx (HZO) has a high surface density (~1014 cm-2) compared to the channel carrier (~1013 cm-2), thereby, ferroelectric polarization induces high electric field near the channel surface, critically impacting on the channel carrier behaviors in metal-ferroelectric-insulator-semiconductor (MFIS) ferroelectric field-effect-transistor (FEFET). In this context, channel mobility degradation by ferroelectric polarization and trapped charges will become a concern, because it is well-known that a huge number of charges (~1014 cm-2) are trapped at the gate stack. Especially, channel mobility during the read operation is required to be discussed, because FEFETs are typically targeted for non-volatile memory applications. In this work, we show that channel mobility (μch) and surface inversion carrier density (Ns,inv) in the n-channel FEFET (nFEFET) during read can be significantly different in the multi-level-cell (MLC) operation. This indicates that trapped carriers significantly degrade mobility and the degradation has a “history” effect, revealing that μch and Ns,inv are determined by overlapped effects of ferroelectric polarization and trapped charges. In addition, it is suggested that ferroelectric polarization induces remote phonon scattering. The complicated device physics of the MFIS FEFET indicates that channel mobility should be carefully modeled in the device simulation.